Synthesis of 2-Nitro-2,3-Unsaturated Glycosides by a Nanomagnetic Catalyst Fe3O4@C@Fe(III) - Yang, Yu; Jiang, Nan; Mei, Yuling; Ding, Zekun; Zhang, Jianbo (Frontiers in Chemistry, 2022)
A sustainable magnetic core-shell nanocatalyst Fe3O4@C@Fe(III) was successfully applied in the synthesis of a series of 2-nitro-2,3-unsaturated O-glycosides with excellent yields (up to 89%) and high stereoselectivity (α:β > 19:1). substrate ranges are widely applicable, including different kinds of alcohols, and even structurally complex acceptors. In addition, phenols could be applied in good yields. Moreover, the catalyst could be easily separated from the reaction by the application of an external magnetic force and reused a minimum of five times without any significant decrease in catalytic performance.